A well‐defined, firm, yellowish‐orange alopecic plaque with multiple whitish papules on the scalp. (18th May 2021) - Nozawa, Y.; Nakamura, Y.; Ono, N.; Hirai, I.; Yashiro, K.; Kameyama, K.; Tanese, K.
Abstract : Click here for the corresponding questions to this CME article.